NUEVO METODO DE CONCENTRACION DE BACILOS DE KOCH - CURIEL R (My University, 1940)
The new method consists of adding acetic acid to sputum in a centrifuge tube to dissolve the mucus Ten cc of physiol saline is added and the mixture shaken for 2 min NaOH is added to neutralize the acidity, and the mixture is centrifuged at high speed
REV MEX MED
Keywords: METODO, CONCENTRACION, BACILOS; CIENCIAS MEDICAS; CIENCIAS CLINICAS; PATOLOCIA CLINICA